2020
DOI: 10.1002/biot.201900404
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR with a Happy Ending: Non‐Templated DNA Repair for Prokaryotic Genome Engineering

Abstract: The exploration of microbial metabolism is expected to support the development of a sustainable economy and tackle several problems related to the burdens of human consumption. Microorganisms have the potential to catalyze processes that are currently unavailable, unsustainable and/or inefficient. Their metabolism can be optimized and further expanded using tools like the clustered regularly interspaced short palindromic repeats and their associated proteins (CRISPR‐Cas) systems. These tools have revolutionize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…coli engineering 38 , does not operate efficiently in Pseudomonas 39 —likely due to limited activity of phage recombinases in these species, or because native proteins interfere with their action. While CRISPR/Cas toolsets accelerated microbial engineering efforts 40 , 41 , non-homologous end joining (NHEJ) mechanisms are virtually absent in prokaryotes 42 , preventing the introduction of frameshifts in target loci—and functional knock-outs thereof. A recent proof-of-principle study on base editing in Pseudomonas by Chen et al 41 .…”
Section: Introductionmentioning
confidence: 99%
“…coli engineering 38 , does not operate efficiently in Pseudomonas 39 —likely due to limited activity of phage recombinases in these species, or because native proteins interfere with their action. While CRISPR/Cas toolsets accelerated microbial engineering efforts 40 , 41 , non-homologous end joining (NHEJ) mechanisms are virtually absent in prokaryotes 42 , preventing the introduction of frameshifts in target loci—and functional knock-outs thereof. A recent proof-of-principle study on base editing in Pseudomonas by Chen et al 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Improved methods of predicting amino acid structure and function have allowed investigators to continue identifying CRISPR-Cas systems from new organisms, therefore growing the field and increasing potential for biotechnological innovation. Some examples include applications in microbial engineering 2 , 3 , agricultural engineering 4 , 5 , novel analyte detection 6 , disease-mediation 7 , stem cell development 8 and viral detection 9 . CRISPR-Cas systems generally fall into two classes based on the number of required Cas components for full function, wherein Class 2 (containing types II, V, and VI) consists of single protein systems that are most useful for biotechnological development due to their relative simplicity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…As CRISPR/Cas12a creates a staggered end resulting a 5‐nt 5′ overhang rather than a blunt cleavage product, which might promote the double‐strand break repair mediated by non‐homologous end joining (NHEJ) and/or microhomology‐mediated end joining (MMEJ) mechanism (Finger‐Bou et al., 2020 ). The initial studies revealed that about 30%˜40% editing efficiency was obtained when targeting ccoO or nifH gene, which was not satisfactory when compared to NHEJ‐mediated CRISPR/Cas in Streptomyces coelicolor (Li et al., 2018 ) and E. coli (Zheng et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%